2019
DOI: 10.3390/su11020321
|View full text |Cite
|
Sign up to set email alerts
|

The Research Topics on E-Grocery: Trends and Existing Gaps

Abstract: The aim of this paper is to analyse through a systematic literature review the main topics studied on a relatively new concept: e-grocery. This study examines the existing literature through the use of some interactive Scopus applications with the goal to provide: (1) a better understanding of the main topics that have been analysed up to now; (2) the principal methodologies that have been used; and (3) the challenges that still exist as well as literature gaps. First, we provide a summary of what has been pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 46 publications
3
38
0
3
Order By: Relevance
“…Attempts to start online grocery sales have also attracted research teams and the number of articles on OGS has increased. Martín et al (2019) observed the yearly increase of studies on OGS from 2000 to 2017 and also pointed that in the marketing area, many studies compared the advantages and disadvantages between e-commerce and physical retail. For instance, Degeratu et al (2000) studied the importance of brand names, Danaher et al (2004) compared brand loyalty of online and offline consumer, Andrews and Currim (2004) or Šarkovská and Chytková (2019) analysed differences in shopping behaviour and Huyghe et al (2016) compared the channels with regards to healthy grocery shopping.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to start online grocery sales have also attracted research teams and the number of articles on OGS has increased. Martín et al (2019) observed the yearly increase of studies on OGS from 2000 to 2017 and also pointed that in the marketing area, many studies compared the advantages and disadvantages between e-commerce and physical retail. For instance, Degeratu et al (2000) studied the importance of brand names, Danaher et al (2004) compared brand loyalty of online and offline consumer, Andrews and Currim (2004) or Šarkovská and Chytková (2019) analysed differences in shopping behaviour and Huyghe et al (2016) compared the channels with regards to healthy grocery shopping.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, most of the recent publications regarding e-grocery deal with assessing, quantifying and benchmarking potential impacts of an increasing e-grocery utilization [12,13,16,17,19,25,27,30,31], analyzing the consumer behavior [3,14,15,24], providing a status quo [7,18,22,23,29] or evaluating the ecologic impact of diverse fulfillment concepts [2,28]. Concerning logistics, several studies propose, conceptualize or examine different models, whereby manifold publications are directly related to assessing or comparing the individual practical impact [6,11,20,21].…”
Section: Grocery Home Deliverymentioning
confidence: 99%
“…Since the beginning of the 21 st century, the relevance of e-grocery has significantly increased in scientific literature [7]. Nevertheless, during our initial literature review in July 2019, where we scanned e-grocery literature in Google Scholar and AISel with the search phrases ("e-grocery" OR "grocery home delivery" OR "online grocery") AND ("Classification" OR "Taxonomy" OR "Structure"), we only found a few articles attempting to classify fulfillment concepts within this context.…”
Section: Structuring and Classifying Grocery Delivery Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Davis and Figliozzi [11] integrated FEVs in their study and calculated economic break-even points, depending on different parameters. Martín et al [19] analyzed trends and research gaps in the field of e-groceries, which can be seen as directly related to the delivery of foodstuffs. Their investigations showed that this research topic plays a minor role in Germany in recent years.…”
Section: Introductionmentioning
confidence: 99%